LACANIAN MATERIALISTIC READING OF THE CHARACTER MARIA SARA OF THE WORK OF JOSÉ SARAMAGO - Betânia da Rocha de Oliveira, Maria (Revista Gênero e Interdisciplinaridade, 2024)
This article analyzes Maria Sara, from the History of the Siege of Lisbon from the perspective of Lacanian materialism of Zižek. The narrative portrays the history of Portugal, but transforms it into an intertextual plot that transcends the literary, creating new narratives by intertwining fiction and reality. Saramago explores the existential and social issues that afflict the human being, reflecting his interest in the historical and the social. Using žižek’s theory, which is based on dialectical and historical materialism, the article examines how these issues manifest themselves in the work, especially through the three instances of the real, imaginary and symbolic. These categories structure the existence of the protagonist in their relationship with Maria Sara and establishes, by extension, the relationship between them and the great other that move their ways in the instance of the symbolic. Thus, the analysis emphasizes how Saramago uses history to discuss human problems from a perspective that goes beyond literary fiction. Fact that attests to Saramago’s unsettling interest in history and social and always in a relationship between the human being and the problems that affect their coexistence in society.